Microbial electrosynthesis system with dual biocathode arrangement for simultaneous acetogenesis, solventogenesis and carbon chain elongation. Issue 30 (26th March 2019) - Vassilev, Igor; Kracke, Frauke; Freguia, Stefano; Keller, Jürg; Krömer, Jens O.; Ledezma, Pablo; Virdis, Bernardino
Abstract : A microbial electrosynthesis cell comprising two biological cathode chambers sharing the same anode compartment is used to promote the production of C2–C4 carboxylic acids and alcohols from carbon dioxide. Abstract : A microbial electrosynthesis cell comprising two biological cathode chambers sharing the same anode compartment is used to promote the production of C2–C4 carboxylic acids and alcohols from carbon dioxide. Each cathode chamber provides ideal pH conditions to favor acetogenesis/carbon chain elongation (pH = 6.9), and solventogenesis (pH = 4.9), respectively, without the requirement of external acid/base dosing.